The Jesus’s parrhesia as a constituent of the "philosophical hero" - Olivares, Benjamín Nicolás (Revista Ethika+, 2020)
The following essay consists of three essential parts whose main aim is to identify and describean authentic parrhesia in Jesus, in the light of the lectures taught by Michel Foucault at theCollègede France. The first and second part are focused on a characterization, contrast, and inquiry theelemental notions that constitute the discourses of truth in Jesus’s ministry. In the third and lastpart, an approach of Jesus with Diogenes and Socrates is presented, and how certain elementsof the presence of cynical parrhesia present in Jesus enable the idea of Jesus as a "philosophical hero".